KONSERVASI TANAMAN PEGAGAN (Centella asiatica L. Urban.) MELALUI TEKNIK IN-VITRO - Dr. Marina Silalahi, M.Si (Jurnal Pro-Life, 2014)
Medicinal plants have been used for centuries Indonesian nation solve a variety of health problems. One type of medicinal plants that have long been used both for traditional and modern medicine is gotu kola (Centella asiatica (L.). Grip is a material that is used to create your +/- 59 species of herbs, with levels of 15-25%. Gotu kola plant part used: roots, stems and leaves are used as a raw material for medicine need for supply of C. asiatica alone reached 12,700 tonnes dry weight per year need is increasing from year to year, leading to the presence in nature and in danger of diminishing. Pegagan of 1993 are included in the list IUCN (International Union for Conservation of Nature and Natural Resources), a category of vulnerable species approaching, so it is vital for conservation. Conservation efforts can be done in situ and ex-situ. Conservation in situ and ex-situ in the field often have problems because habitat destruction and overexploitation. efficient alternative for the ex situ conservation is through the technique of in-vitro. Culture is the technique of in-vitro cultivation of cells, tissues, and organs that have been separated from their natural environment and grown in an artificial medium under conditions appropriate sterile. Application of in vitro storage of C. asiatica through storage in a state of growth (short-term), minimal growth storage (short and medium term) and storage by freezing (long-term).